(Re)membering the nation's "forgotten" past: Portrayals of Gukurahundi in Zimbabwean literature. (June 2017) - Ncube, Gibson; Siziba, Gugulethu
In the early 1980s Zimbabwe witnessed an ethnic cleansing which has been ignored in official state discourses and rendered unspeakable. This "moment of madness" (Ellis, 2006: 40), as Robert Mugabe called it, has come to be referred to as Gukurahundi . The minority Ndebele tribe was persecuted by government-backed forces. This article draws on the theoretical reflections of El Nossery and Hubbell who argue that even though some traumatic experiences may be unspeakable, they are not necessarily unrepresentable. Through an analysis of Yvonne Vera's The Stone Virgins (2002), Christopher Mlalazi's novel Running with Mother (2012), several poems by John Eppel as well as Owen Maseko's paintings, this paper contends that these works of art broach a subject which has been rendered quasi-taboo. It is argued that these works of literature fictionalize, against the grain of the official national narrative, Zimbabwe's traumatic postcolonial violence in which the national army turned against the country's citizens under the guise of weeding out "dissidents" in the immediate post-independence period. Moreover, this article contends that fictional and artistic works function in such a way as to keep the memory of civilian victims alive, to heal the national trauma through memorializing it, and to call perpetrators to account by pointing out their culpability.